Pemberdayaan Masyarakat Dalam Pelatihan Softskill PHBS Pada Ibu di Kelurahan Ladang Bambu Kecamatan Medan Tuntungan - Siregar, Julaiha; Sopiah, Sopiah (Indonesian Journal Publisher, 2022)
Creating a healthy life is actually very easy, compared to the costs that must be spent on treatment if you experience health problems. So, healthy living behavior should be implemented by every individual, especially mothers. The community service method is carried out through counseling, discussions and health checks as well as teaching correct hand washing related to soft skills to mothers in Ladang Bambu Village, Medan Tuntungan District. The aim of this community service activity is to illustrate to mothers the importance of implementing clean and healthy living behavior to avoid disease. The following is an attachment to our outreach activity agenda. The Preparation Stage was carried out by conveying to the Government of Ladang Bambu Subdistrict, Medan Tuntungan District about what would be done, then we created an Extension Event Unit (SAP), as well as preparing materials and tools that would be used, for example Tensimeters and Leaflets. Implementation Stage We came to Ladang Bambu Village, Medan Tuntungan District to make preparations, clean the place that will be used. Mothers are gathered at the place directed by us. After everything was ready, the activity started with my colleague as moderator to open the counseling. For this reason, counseling or information related to clean and healthy PHBS living behavior is provided to mothers, so that awareness grows of the importance of implementing clean and healthy PHBS living behavior among mothers for the health and welfare of family members. Mother's soft skills regarding PHBS and it is recommended to check her health regularly.